Burning mouth syndrome in patients wearing prothesis: Evaluation of type I and type II - (:unkn) unknown (My University, 2005)
Burning mouth syndrome (BMS) is a fairly common condition: typically patients complain of a burning sensation affecting the oral mucosa that appears clinically normal. The history given by patients with BMS falls into two broad categories: patients complain either of burning not present on waking but which develops as the day goes on and is worse in the evening (Type I) or of a constant burning (Type II); in both cases burning is unremitting. We evaluated 57 patients, who complained of burning over a 41/2-year-period. The present study aimed to determine the description of the pattern of the burning sensation by denture wearing patients with Type I and Type II BMS and to evaluate age, sex, history of symptoms, laboratory results and location. © 2005 VSP.
Keywords: BMS Type I; BMS Type II; Burning mouth syndrome; Psychology